2009
DOI: 10.1007/s11172-009-0205-1
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of ferrocene oxidation under the conditions of electrospray ionization

Abstract: The formation of molecular ions of ferrocene is detected under the «inverse» conditions of electrospray ionization where the pure solvent alone is electrosprayed in the presence of fer rocene vapor. The quantum chemical calculations using the B3LYP/LanL2DZ method suggest that the ferrocene oxidation occurs in the gas phase and follows the mechanism of activating protonation where a protonated molecule acts as an oxidant for another ferrocene molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…So, in the case of protonated benzoylferrocene, it is reasonable to proposed that within the [benzoyl/ferrocene] ion‐neutral complex intermediate, an electron is transferred from the neutral ferrocene to the benzoyl cation leading to the formation of the ferrocinium cation, where the divalent iron, Fe(II), is oxidized to the trivalent iron, Fe(III). Moreover, by the help of DFT calculations, Rodionov's group has found that under ESI conditions the initial ferrocene derivative molecules were oxidized by the protonated ones to form molecular ions . It is sound to propose that ferrocene‐containing substances are facile to participate in redox processes in the gas phase as they do in the solid and liquid phase .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So, in the case of protonated benzoylferrocene, it is reasonable to proposed that within the [benzoyl/ferrocene] ion‐neutral complex intermediate, an electron is transferred from the neutral ferrocene to the benzoyl cation leading to the formation of the ferrocinium cation, where the divalent iron, Fe(II), is oxidized to the trivalent iron, Fe(III). Moreover, by the help of DFT calculations, Rodionov's group has found that under ESI conditions the initial ferrocene derivative molecules were oxidized by the protonated ones to form molecular ions . It is sound to propose that ferrocene‐containing substances are facile to participate in redox processes in the gas phase as they do in the solid and liquid phase .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, by the help of DFT calculations, Rodionov's group has found that under ESI conditions the initial ferrocene derivative molecules were oxidized by the protonated ones to form molecular ions. [10,11] It is sound to propose that ferrocene-containing substances are facile to participate in redox processes in the gas phase as they do in the solid and liquid phase. [5,24] A schematic potential energy surface of the model compound benzoylferrocene is given in Fig.…”
Section: Single Electron Redox By Ion-neutral Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note, that the process of protonation and, hence, subsequent interconversions takes place mainly in a gas phase, as is testified by the experiments with the deuterated solvents, as well as by the mass-spectra of ferrocene [9] and ferrocenylmethyldimethylamine, obtained under the ''inverse" ESI Fig. 3.…”
Section: Ionmentioning
confidence: 88%
“…in this case the protonation of methanol in a gas phase is fulfilled by hydroxonium ions. Recently, [9] it has been discovered by us that the ferrocene molecular ions are formed under the ''inverse" ESI conditions when the ferrocene vapors are situated in the ion source, and only clean acetonitrile is subjected to electrospraying. By the help of quantum-chemical calculations it has been found, that under these conditions the ferrocene oxidation occurs in the gas phase according to the scheme of activating protonation, when the protonated molecule is the oxidizer of the initial ferrocene molecule, and the role of electrochemistry in the process of the electrospraying consists in generation of hydroxonium ions, which protonate the ferrocene molecules in the gas phase [9].…”
Section: Introductionmentioning
confidence: 99%